Analysis Of The Effect Of Corporate Governance Structure And Financial Distress - Alrahmani Trisari; Kun Ismawati; Astrid Widayani (International Conference On Digital Advanced Tourism Management And Technology, 2023)
The purpose of this study is to see the influence of corporate governance structure (independent commissioner, audit committee, institutional ownership, managerial ownership) and financial distress on the integrity of financial statements of studies on manufacturing companies listed on the IDX for the 2017-2021 period. In this study, quantitative methods were used with secondary data obtained by collecting financial statement data for all manufacturing companies listed on the IDX for the 2017-2021 period, with the use of purposive sampling techniques, sample selection with predetermined criteria so that samples of 40 companies with 5 years of period were obtained with 200 samples. The study used SPSS data processing applications with analytical methods multiple linear regression. The results of the hypothesis test in this study found that independent commissioners, audit committees have no influence on the integrity of financial statements. On the contrary, institutional ownership, managerial ownership and financial distress have an influence on the integrity of financial statements. The results of the F test prove simultaneously that the variables of independent commissioner, audit committee, institutional ownership, managerial ownership, and financial distress affect the integrity of financial statements.